Abdominal pain in a 5-year-old boy. (9th June 2011) - Thompson, Rebecca; Kothandaraman, Vijayalakshmi
Abstract : A 5-year-old male presented with a 1-day history of vomiting, epigastric pain, loose stools and poor oral intake. The child had intermittent symptoms of abdominal pain and vomiting for the past 2 years and there was a strong family history of chronic hereditary pancreatitis. A random serum amylase was elevated at 2320 IU/l. Abdominal ultrasound scan revealed no abnormalities. On the basis of the family history, positive symptoms and elevated amylase, a diagnosis of hereditary pancreatitis was made. The child received symptomatic management and treatment for his acute illness. He is currently awaiting results from molecular testing.